Banned drugs: Still available in India - Manjari Gupta; Anil Ghom; F M Debta; Sunil Vyas; Abhijeet Deoghare; Prashant Gupta; Shantala Gupta (Wolters Kluwer Medknow Publications, 2011)
Drugs undergo rigorous testing before they are introduced into the market. The efficacy as well as safety profiles of the drug are tested, adverse effects of drugs appear only after the drug is used in the general population. These adverse effects are detected through pharmacovigilance. If the adverse effects are severe or the risks of using the drug outweigh the benefits, the country bans the drug. Some drugs may cause adverse effects only when combined with particular drugs. In such cases, only the fixed dose combination is banned and not the individual drugs. This article is related to banned drugs and the products which are still used in medical fraternity.